2017
DOI: 10.1093/hmg/ddx078
|View full text |Cite
|
Sign up to set email alerts
|

EIF4A3 deficient human iPSCs and mouse models demonstrate neural crest defects that underlie Richieri-Costa-Pereira syndrome

Abstract: Biallelic loss-of-function mutations in the RNA-binding protein EIF4A3 cause Richieri-Costa-Pereira syndrome (RCPS), an autosomal recessive condition mainly characterized by craniofacial and limb malformations. However, the pathogenic cellular mechanisms responsible for this syndrome are entirely unknown. Here, we used two complementary approaches, patient-derived induced pluripotent stem cells (iPSCs) and conditional Eif4a3 mouse models, to demonstrate that defective neural crest cell (NCC) development explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 50 publications
4
57
3
2
Order By: Relevance
“…真核生物蛋白翻译过程需要多个因子的参与 [5] . ; eIF4A3与胚胎的早期发育相关 [7] . 研究发 现, eIF4B和eIF4E的表达能够增强eIF4A1的活性 [8] , 而 肿瘤抑制子PDCD4能抑制其功能 [9] .…”
unclassified
“…真核生物蛋白翻译过程需要多个因子的参与 [5] . ; eIF4A3与胚胎的早期发育相关 [7] . 研究发 现, eIF4B和eIF4E的表达能够增强eIF4A1的活性 [8] , 而 肿瘤抑制子PDCD4能抑制其功能 [9] .…”
unclassified
“…with the typical immunophenotype, which gave rise to osteoblasts, chondrocytes and adipocytes (Miller et al 2017). Taken together, these data demonstrated that our strategy efficiently yielded disease-relevant cell types, which allowed us to assess cellular and molecular phenotypes associated with RCPS in vitro.…”
Section: Discussionmentioning
confidence: 59%
“…Despite presenting phenotypes comparable to humans, whose EIF4A3 levels are varied depending on cell type, Eif4a3 haploinsufficient mice also displayed severe phenotypes not so far described in humans (Miller et al 2017). These phenotypic differences could be due to Cre efficiency or because humans are genetically diverse whereas mice are inbred, which exposes phenotypes that are normally masked in humans.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations